PERBANDINGAN BEBERAPA METODE PERHITUNGAN DEBIT PUNCAK BANJIR RANCANGAN - HUMAIRO SAIDAH; ATAS PRACOYO; KHAIRUDIN KHAIRUDIN (GANEC SWARA, 2020)
Peak discharge flood analysis is very crucial in waterworks design. The proper design flood discharge will produce effective construction dimensions as project requirement. Therefore, flood design calculations must be analyzed using appropriate methods. The problem in estimating design flood discharge is usually found in ungauged watersheds which do not have any water discharge measuring equipment.This study wants to test the flood design method using rain data input to be applied to the Babak River, so the result can be used as a guide in the selection of flood discharge calculation techniques in other ungauged watersheds.The accuracy test is carried out by comparing the results of these methods with the flood design resulted from a frequency analysis of the Annual Maximum Series. Based on the results of the calculation, the peak flood of the Harpers method has the smallest RE and RMSEP values are 8.960% and 88.546 respectively. Thus, it can be concluded that the calculation of the design of the flood peak Haspers method has the best accuracy of the analysis results when compared with the Melchior and Weduwen methods for Babak River.